Impact of natural re-oxygenation on the sediment dynamics of manganese, iron and phosphorus in a euxinic Baltic Sea basin. (1st February 2019) - Hermans, Martijn; Lenstra, Wytze K.; van Helmond, Niels A.G.M.; Behrends, Thilo; Egger, Matthias; Séguret, Marie J.M.; Gustafsson, Erik; Gustafsson, Bo G.; Slomp, Caroline P.
Abstract: The Baltic Sea is characterized by the largest area of hypoxic (oxygen (O2 ) < 2 mg L −1 ) bottom waters in the world's ocean induced by human activities. Natural ventilation of these O2 -depleted waters largely depends on episodic Major Baltic Inflows from the adjacent North Sea. In 2014 and 2015, two such inflows led to a strong rise in O2 and decline in phosphate (HPO4 2− ) in waters below 125 m depth in the Eastern Gotland Basin. This provided the opportunity to assess the impact of such re-oxygenation events on the cycles of manganese (Mn), iron (Fe) and phosphorus (P) in the sediment for the first time. We demonstrate that the re-oxygenation induced the activity of sulphur (S)-oxidising bacteria, known as Beggiatoaceae in the surface sediment where a thin oxic and suboxic layer developed. At the two deepest sites, strong enrichments of total Mn and to a lesser extent Fe oxides and P were observed in this surface layer. A combination of sequential sediment extractions and synchrotron-based X-ray spectroscopy revealed evidence for the abundant presence of P-bearing rhodochrosite and Mn(II) phosphates. In contrast to what is typically assumed, the formation of Fe oxides in the surface sediment was limited. We attribute this lack of Fe oxide formation to the high flux of reductants, such as sulphide, from deeper sediments which allows Fe(II) in the form of FeS to be preserved and restricts the penetration of O2 into the sediment. We estimate that enhanced P sequestration in surface sediments accounts for only ∼5% of water column HPO4 2− removal in the Eastern Gotland Basin linked to the recent inflows. The remaining HPO4 2− was transported to adjacent areas in the Baltic Sea. Our results highlight that the benthic O2 demand arising from the accumulation of organic-rich sediments over several decades, the legacy of hypoxia, has major implications for the biogeochemical response of euxinic basins to re-oxygenation. In particular, P sequestration in the sediment in association with Fe oxides is limited. This implies that artificial ventilation projects that aim at removing water column HPO4 2− and thereby improving water quality in the Baltic Sea will likely not have the desired effect.